A gatifloxacin-loaded controllable nanohydrogel and use of the same in preparation of a drug for treating keratitis
Patent Information
- Application Number
- CN202410120062.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-01-29
AI Technical Summary
然而,传统滴眼液的生物利用度较差,增加给药的频率和剂量可能导致细菌耐药性和累积性全身副作用的风险增加
[0032]1、以硼砂为催化剂,对PEG进行了硫醇-烯迈克尔型聚加成反应。硼砂作为催化剂非常高效,可在室温条件下快速凝胶化(从40s到2min)。从本质上讲,硼砂作为一种催化剂,可同时形成两类键:共价硫醚键和瞬态硼酸酯键。由于硼酸酯键的动态性,使得凝胶具有自愈性,在没有外部刺激的情况下,凝胶可在30min内愈合。所制备出的PDB纳米水凝胶具有良好的孔隙率、热敏性、黏度分布、流变特性和较高的细胞相容性。
Smart Images

Figure CN117959243B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a gatifloxacin-loaded controllable nanohydrogel and its use in treating keratitis. Specifically, it relates to a gatifloxacin-loaded polyethylene glycol-dithiothreitol-boric acid (PDB) nanohydrogel and its use in preparing a drug delivery system for treating bacterial keratitis. Background Technology
[0002] Keratitis is an infectious corneal disease caused by bacterial, viral, fungal, or parasitic infections and immune-related complications, and is one of the leading causes of blindness in my country. Bacterial keratitis is the most common, accounting for approximately 65% to 90% of all cases. Bacterial keratitis often occurs after corneal trauma, allowing pathogens to invade the exposed corneal tissue, leading to a severe inflammatory reaction. Gatifloxacin, a fourth-generation fluoroquinolone antibiotic, is known for its excellent antibacterial efficacy and strong inhibitory activity against Gram-positive bacteria and atypical pathogens, making it a good choice for treating bacterial keratitis. However, compared to other fluoroquinolone antibiotics such as moxifloxacin and levofloxacin, gatifloxacin has relatively poor corneal permeability. Factors such as blinking, tear drainage, and conjunctival absorption further shorten the residence time of gatifloxacin on the ocular surface. Achieving high utilization through routine topical administration is challenging, and high doses or frequent use of gatifloxacin can lead to serious side effects such as dyspnea and cardiac arrhythmias.
[0003] Due to the unique physiological structure of the eye, medications cannot be effectively delivered to ischemic areas of the eyeball via the bloodstream. Therefore, oral or intravenous administration is generally not recommended; instead, topical administration, such as eye drops and ointments, is used for treatment. However, traditional eye drops have poor bioavailability, and increasing the frequency and dosage of administration may lead to an increased risk of bacterial resistance and cumulative systemic side effects.
[0004] Nanogels are biocompatible biomaterials with a three-dimensional network structure that can swell in water without dissolving. Their nanoscale size and porous structure allow for the physical encapsulation of drugs within their cavities, thus enabling drug delivery. pH-responsive nanogel drug carriers utilize changes in the intracellular pH microenvironment induced by nanogel conditions to control and trigger drug release, thereby improving drug bioavailability and therapeutic efficacy. Li et al. reported a method for preparing pH-responsive drug carriers, using hydrophilic methoxy polyethylene glycol-poly[N-(N-(2-aminoethyl)-2-aminoethyl)-L-glutamic acid] and hydrophobic terephthalaldehyde as crosslinking agents (Li, Y.; Bui, QN; Duy, LTM; Yang, HY, Lee, DSOne-Step Preparation of pH-Responsive Polymeric Nanogels as Intelligent Drug Delivery Systems for Tumor Therapy[J]. Biomacromolecules, 2018 19(6), 2062-2070.). These nanogels exhibit stability at pH 7.4, while simultaneously degrading and rapidly releasing drugs under simulated acidic conditions. Studies have previously prepared gatifloxacin-loaded P(HEMA-co-MAA) hydrogels, which can be used as ocular surface contact lenses and have shown good efficacy in treating Staphylococcus aureus-induced keratitis (Shi, Y.; Lv, H.; Fu, Y.; Lu, Q.; Zhong, J.; Ma, D.; Huang, Y., Xue, W. Preparation and characterization of a hydrogel carrier to deliver gatifloxacin and its application as a therapeutic contact lens for bacterial keratitis therapy[J]. Biomed Mater, 2013 8(5), 055007.).
[0005] Polyethylene glycol (PEG) is a polymer that is widely used in the preparation of nanohydrogel drug delivery systems due to its excellent biocompatibility, dispersibility, adhesion and low immunogenicity / antigenicity [26, 27]. Dithiothreitol (DTT) is a small molecule organic reducing agent that can be used as a reducing agent and deprotecting agent for thiolated DNA. In particular, when DTT is added to PEG hydrogels, the hydrogels exhibit better biocompatibility, making them more suitable for tissue repair
[27] . Borax (sodium borate decahydrate, Na2B4O7·10H2O) is a non-toxic food additive and a suitable choice for chemical crosslinking agents due to its low toxicity, low cost, and good water solubility [28, 29]. Borax has been reported to be successfully used to crosslink polyvinyl alcohol and other hydrogels [30-32]. In addition, borax can also be used as a catalyst for the Michael addition reaction between PEGDA (polyethylene glycol diacrylate) and DTT [27, 29] (Ai, Y.; She, W.; Wu, S.; Shao, Q.; Jiang, Z.; Chen, P.; Mei, L.; Zou, C.; Peng, Y., He, Y. AM1241-Loaded Poly(ethylene glycol)-Dithiothreitol Hydrogel Repairs CranialBone Defects by Promoting Vascular Endothelial Growth) Factor and COL-1 Expression[J]. Front Cell Dev Biol, 202210888598., He, L.; Szopinski, D.; Wu, Y.; Luinstra, GA, Theato, P. Toward Self-Healing Hydrogels Using One-Pot Thiol-EneClick and Borax-Diol Chemistry[J]. ACS Macro Lett, 20154(7), 673-678.). Therefore, there is a need to develop an effective ocular drug delivery system with excellent thermosensitivity and pH responsiveness, suitable for use as eye drops, while having a lower dosing frequency and smaller dose, exhibiting higher drug release efficiency, and superior therapeutic effect on bacterial keratitis. Summary of the Invention
[0006] The purpose of this invention is to provide a rate-controlled polyethylene glycol-dithiothreitol-boric acid (PDB) nanohydrogel carrier loaded with gatifloxacin. This nanohydrogel carrier possesses good porosity, thermosensitivity, viscosity distribution, rheological properties, and high cell compatibility, while maintaining appropriate swelling and stability. It exhibits a high drug release rate under acidic conditions, effectively enhancing drug retention, utilization, and antibacterial effects on the ocular surface, and is used to treat bacterial keratitis.
[0007] The technical solution of the present invention is as follows:
[0008] One technical solution of the present invention relates to a controllable nanohydrogel capable of loading drugs. The nanohydrogel is synthesized using borax as a catalyst through a polymerization reaction between polyethylene glycol dimethacrylate (PEGDA) and dithiothreitol (DTT) and a complexation reaction between tetrahedra, resulting in a polyethylene glycol-dithiothreitol-boric acid (PDB) nanohydrogel. It exhibits good porosity, thermosensitivity, viscosity distribution, rheological properties, and high cell compatibility, making it suitable for corneal drug delivery. More preferably, PEGDA and DTT are added in a 1:1 ratio to form a three-dimensional cross-linked network nanohydrogel, and the borax to DTT ratio is 1:7 to prepare a drip-compatible thermosensitive nanohydrogel with excellent performance. Even more preferably, the nanohydrogel has an average diameter of 124.9 nm, a zeta potential of -23.3 mV, and a VAC-NPS of 10 at 37°C. -4 Up to 10 -1 It exhibits good viscosity distribution within the range of Pa·s. Further preferred, the loaded drug is gatifloxacin.
[0009] The PDB nanohydrogels were characterized using the methods described above:
[0010] (1) The chemical structure and composition of the hydrogel were confirmed by proton nuclear magnetic resonance (1H-NMR) and Fourier transform infrared (FTIR) spectroscopy.
[0011] (2) The temperature-sensitive changes of PDB nanohydrogel were analyzed by the test tube inversion method.
[0012] (3) Scanning electron microscopy (SEM) was used to analyze the surface morphology of the hydrogel.
[0013] (4) The rheological properties of hydrogels were studied using small amplitude oscillating shear flow (SAOS) experiments.
[0014] (5) The synthesized PDB nanohydrogel was tested using a laser particle size analyzer and a zeta potential analyzer.
[0015] Experiments show that PDB nanohydrogels have good porosity, thermosensitivity, viscosity distribution, rheological properties and high cell compatibility.
[0016] PDB nanohydrogels have a small and uniform size distribution, no obvious aggregation, an average particle size of 124.9 nm, and a zeta potential of approximately -23.3 mV.
[0017] At 37℃, the PDB nanohydrogel exists in a gel state. As the temperature decreases to 4℃, the PDB nanohydrogel gradually changes from a gel state to a liquid state. Upon heating back to 37℃, the PDB nanohydrogel returns to a gel state.
[0018] Another technical solution of the present invention relates to a method for preparing PDB nanohydrogels, comprising the following steps:
[0019] (1) Dissolve 0.14 mM PEDDA and 0.14 mM DTT in 0.5 ml of water;
[0020] (2) Add 0.5 ml of 0.04 mmol / L sodium borate solution. After thorough mixing, keep the solution at room temperature for a short time to obtain PDB nanohydrogel.
[0021] Another aspect of this invention relates to the use of drug-loadable PDB nanohydrogels in the preparation of drug delivery systems for treating bacterial keratitis. Preferably, it is used as eye drops.
[0022] Another technical solution of the present invention relates to a drug delivery system for a controllable nanohydrogel loaded with gatifloxacin. The drug-loadable PDB nanohydrogel is uniformly dispersed in PBS at 4°C and stirred overnight. Then, gatifloxacin is added to the above solution at 4°C and mixed thoroughly to prepare a PDB nanohydrogel drug delivery system.
[0023] The physicochemical properties of the drug-loaded PDB nanohydrogel were investigated by scanning electron microscopy, swelling ratio determination, pore distribution determination, particle size, potential, gelation temperature, and in vitro degradation. The drug delivery system under acidic and alkaline conditions and the effects of its structure and composition on drug encapsulation efficiency and in vitro sustained-release behavior were investigated by dialysis using pH 7.4 / 5.5 PBS phosphate buffer as the release medium.
[0024] An in vitro cell model was constructed using SDHCEC cells to test the cell compatibility of PDB nanohydrogels. After 48 hours of in vitro culture, the obtained hydrogels were observed for cell adhesion and proliferation using scanning electron microscopy (SEM) (PHILIPS, ESEM XL 30, Holland) to determine the effect of PDB nanohydrogels on corneal epithelial cells.
[0025] A bacterial keratitis mouse model was established by inducing keratitis through local scraping and inoculation of Staphylococcus aureus in the right eye of BALB / c mice. PDB nanohydrogels were prepared, and GFLX-loaded PDB nanohydrogels were dropped onto the mouse corneas. Histological examination (hematoxylin-eosin staining) of the cornea was used to evaluate the therapeutic efficacy of the PDB nanohydrogels against bacterial keratitis. The antibacterial effect of the gatifloxacin-loaded PDB hydrogels was determined by culturing mouse tears on a culture medium and observing bacterial growth on the medium.
[0026] Compared to PDB nanohydrogels, the microstructure of the gatifloxacin-loaded PDB nanohydrogels did not show significant changes and retained their porosity. The drug-loaded PDB nanohydrogels had a Z-average size of 121.7 nm and a zeta potential of -24.1 mV. Furthermore, their thermosensitive properties remained unchanged. At 37 °C, the drug-loaded PDB nanohydrogels were in a gel state, gradually transitioning to a liquid state as the temperature decreased to 4 °C. These data indicate that the properties of the PDB nanohydrogels are essentially unaffected after drug loading.
[0027] The in vitro release behavior of the drug-loaded nanohydrogel showed that the swelling rate of the drug-loaded PDB nanohydrogel reached a plateau after approximately 12 hours, with a measured swelling rate of about 21.2%. This indicates that the drug-loaded nanohydrogel exhibits low swelling rate and minimal porosity change after water absorption, thus enabling slow and stable drug release.
[0028] The in vitro degradation rate and release behavior of the drug-loaded PDB nanohydrogel under different pH conditions indicate that the drug-loaded PDB nanohydrogel exhibits good stability under simulated physiological conditions. After 21 days, the degradation rate in simulated body fluid at pH 5.5 was approximately 45.7%, while the degradation rate in simulated body fluid at pH 7.4 was approximately 37.8%. The in vitro drug release behavior of the drug-loaded PDB nanohydrogel shows that the drug release rate is significantly higher under acidic conditions compared to a neutral environment. Furthermore, the release behavior shows no burst release; the drug release rate is approximately 37.6% within 24 hours at pH 5.5 and approximately 16.2% at pH 7.4. These results indicate that the PDB nanohydrogel loaded with gatifloxacin possesses good swelling properties, stability, and pH responsiveness, effectively prolonging the drug's residence time on the ocular surface and improving its bioavailability.
[0029] Another technical solution of the present invention relates to the application of a drug delivery system for a controllable nanohydrogel loaded with gatimicin in the preparation of eye drops for treating bacterial keratitis.
[0030] Regarding the in vivo targeted distribution and efficacy of gatifloxacin-loaded controlled-release nanohydrogels in the treatment of bacterial keratitis, the PDB nanohydrogel group showed no significant change in corneal thickness after treatment, but the interruption of intercellular connections, increased intercellular spaces, and keratinization were alleviated and slightly improved. Compared with the model group, the gatifloxacin-loaded PDB nanohydrogel group showed significant improvement in corneal opacity, reduced corneal thickness, no obvious keratinization, and improved intercellular connection interruption, increased intercellular spaces, and uneven cell size. Regarding antibacterial effects, gatifloxacin, PDB nanohydrogels, and gatifloxacin-loaded PDB nanohydrogels all showed varying degrees of inhibition on the growth of Staphylococcus aureus in tears, with the gatifloxacin-loaded PDB nanohydrogel showing the best inhibitory effect. These results indicate that PDB nanohydrogels can serve as an excellent sustained-release system for gatifloxacin, prolonging the drug's duration of action and enhancing its efficacy. Furthermore, PDB nanohydrogels exhibit good biocompatibility, significantly improving the efficacy of gatifloxacin in the treatment of bacterial keratitis.
[0031] The beneficial effects of this invention are:
[0032] 1. Borax was used as a catalyst to induce a thiol-olefin Michaelis-Glaucus polyaddition reaction of PEG. Borax is a highly efficient catalyst, enabling rapid gelation at room temperature (from 40 s to 2 min). Essentially, borax, as a catalyst, can simultaneously form two types of bonds: covalent thioether bonds and transient borate ester bonds. Due to the dynamic nature of the borate ester bonds, the gel exhibits self-healing properties, healing within 30 min without external stimulation. The prepared PDB nanohydrogel possesses good porosity, thermosensitivity, viscosity distribution, rheological properties, and high cell compatibility.
[0033] 2. PDB nanohydrogel drug delivery system combined with antibiotic drugs. Under appropriate ratio control, PDB nanohydrogels exhibit sensitive temperature-sensitive and pH-responsive properties. Before instillation, they exist as a homogeneous liquid. When applied to the ocular surface as eye drops, they rapidly cross-link under temperature, forming a stable three-dimensional network structure that encapsulates the drug. Furthermore, due to their pH responsiveness, drug release is accelerated under acidic conditions and virtually nonexistent under neutral conditions, further enhancing the pH specificity of drug release.
[0034] 3. Gatifloxacin, an antibiotic, is used as a targeted therapy for bacterial keratitis. The nano-hydrogel, through local coverage, provides continuous and controllable release and distribution of gatifloxacin at the infected site, ensuring effective drug delivery into cells and direct delivery to the infection site. This reduces the required dosage, improves bioavailability, and lowers toxic side effects.
[0035] 4. Animal experiments have shown that, compared with gatifloxacin eye drops, gatifloxacin-loaded PDB nanohydrogel exhibits superior therapeutic effects and demonstrates stronger antibacterial capabilities.
[0036] 5. Compared with gatifloxacin-loaded P(HEMA-co-MAA) hydrogels, the gatifloxacin-loaded PDB nanohydrogels prepared in this study exhibit thermosensitivity and pH responsiveness, making them suitable for use as eye drops. They also demonstrate higher drug release efficiency at the site of infection compared to normal sites. Attached Figure Description
[0037] Figure 1 This is the identification of PDB nanohydrogels. (A) FTIR spectra of PEGDA (black line in the figure), DTT (blue line in the figure), and PDB (red line in the figure); (B) 1H NMR spectra of PEGDA (red line in the figure), DTT (blue line in the figure), and PDB (black line in the figure).
[0038] Figure 2 Characterization of PDB nanohydrogels. (A) SEM image of PDB nanohydrogels; (B) Thermosensitive properties of PDB nanohydrogels; (C) Sol-gel phase variation curves of PDB nanohydrogels with temperature and concentration; (D) Particle size of PDB nanohydrogels; (E) Zeta potential of PDB nanohydrogels; (F) Viscosity distribution of PDB nanohydrogels; (G) Immunofluorescence assay of biocompatibility of PDB nanohydrogels.
[0039] Figure 3 This study investigates the properties and drug release of drug-loaded PDB nanohydrogels. (A) SEM image of the drug-loaded PDB nanohydrogels; (B) Temperature-sensitive properties of the drug-loaded PDB nanohydrogels; (C) Particle size of the drug-loaded PDB nanohydrogels; (E) Zeta potential of the drug-loaded PDB nanohydrogels; (D) Viscosity distribution of the PDB nanohydrogels; (E) Swelling rate of the drug-loaded PDBs; (F) In vitro degradation rate of the drug-loaded PDBs; (G) In vitro drug release curve of the drug-loaded PDBs.
[0040] Figure 4 This study examines the efficacy of controllable nanohydrogels encapsulating gatifloxacin in the treatment of bacterial keratitis. (A) Clinical manifestations and histology of mouse corneas before and after bacterial infection; (B) Bacterial culture of tears extracted on agar plates. Detailed Implementation
[0041] The present invention will be further illustrated by way of examples, but the present invention is not limited to the following examples.
[0042] Statistical analysis and graphical representation of all data in this study were performed using GraphPad Prism 8 software. All data are expressed as the mean of the standard deviations (SD) of at least three independent experiments.
[0043] Example 1: Preparation and characterization of PDB nanohydrogels
[0044] 1.1 Preparation of PDB nanohydrogel of the present invention
[0045] PDB nanohydrogels were prepared by using borax (Sigma, America) as a catalyst and by polymerizing PEGDA (Aladdin, China) and DTT (Aladdin, China) and complexing DTT with borate anion (B(OH)4-) and 1,2-diol to form polymer chains and a three-dimensional cross-linked hydrogel network.
[0046] First, 0.14 mM PEDDA and 0.14 mM DTT were dissolved in 0.5 ml of water, and then 0.5 ml of 0.04 mmol / L sodium borate solution was added. After thorough mixing, the solution was kept at room temperature for a short time to obtain PDB nanohydrogel.
[0047] 1.2 Identification of PDB nanohydrogels
[0048] like Figure 1 As shown in Figure A, after the Michael addition reaction, the absorptions of C=C at 1625 cm⁻¹ and -SH at 2549 cm⁻¹ almost disappear, indicating that the functional groups are completely consumed during the reaction. Figure 1 In section B, the 1H NMR spectrum shows that multiple peaks (a) corresponding to CH2=CH- completely disappear from 6.0 ppm to 6.5 ppm. Simultaneously, a new sharp peak appears near 5.0 ppm, attributed to the methylene proton (-CH2COO-) of the Michael addition product, further confirming the complete consumption of the activated C=C double bond within a short time. Figure 1 B). These data demonstrate the successful synthesis of PDB nanohydrogels.
[0049] 2. Characterization of PDB nanohydrogels
[0050] 2.1 Method
[0051] (1) The chemical structure and composition of the hydrogel were confirmed using Fourier transform infrared spectroscopy (FTIR) (Bruker, Germany) and nuclear magnetic resonance (NMR) spectroscopy (QOne Instruments, China). Fourier transform infrared spectroscopy (FTIR) was used to detect characteristic functional groups in the sample in the range of 4000 cm⁻¹ to 500 cm⁻¹. The sample was dissolved in deuterium oxide for 1H-NMR measurements.
[0052] (2) Microstructure analysis of the hydrogel was performed using scanning electron microscopy (SEM) (Phenom, Netherlands). 10 μl of the gel sample was diluted and completely dissolved in 1 ml of water. The 10 μl solution was then allowed to air dry. The dried sample was fixed onto a conductive adhesive on a sample holder, followed by a 2-minute gold sputtering coating to ensure complete conductivity. The sample was then observed under SEM.
[0053] (3) The PDB nanogel was completely dissolved in phosphate-buffered saline (PBS). The nanogel was diluted in PBS to prepare sols of different concentrations: 10%, 20%, 25%, 30%, and 35%. The solutions were stirred overnight at 0°C. Then, 200 μL of each solution was transferred to 2.0 mL test tubes, and two parallel samples were prepared for each concentration. The temperature was increased from 5°C to 80°C, increasing by 2°C every 10 minutes. Tilting the test tubes indicated a phase transition from the sol to the gel state; if the liquid did not flow, it indicated a phase transition of the copolymer from the sol state to the gel state. The temperatures at which the phase transition occurred for each concentration were recorded, and phase diagrams were plotted based on the data. The state of the PDB nanogel relative to temperature was analyzed using the inverted test tube method.
[0054] (4) The synthesized PDB nanohydrogel was prepared into a uniformly dispersed transparent solution and tested using a laser particle size analyzer (Malvern, UK). The PDB nanohydrogel was dispersed in a solvent to form a uniform and transparent solution, and then particle size analysis was performed using a laser particle size analyzer. The measurement data were recorded and analyzed.
[0055] (5) The rheological properties of the nanohydrogels were studied using small amplitude oscillating shear (SAOS) experiments. Rheological measurements were performed on a rheometer (TA Instruments, USA). The hydrogel sample to be tested was uniformly coated onto the stage of the rotary rheometer. The temperature was set to 37℃, and the frequency range was set to 0.1 to 100 rad·s⁻¹. Data were recorded, and viscosity distribution curves were plotted based on the measurement results.
[0056] 2.2 Results
[0057] like Figure 2As shown in Figure A, the PDB nanohydrogel exhibits a porous morphology with smooth pore walls, and the pore sizes vary. This is a typical structure for polymer hydrogels, giving PDB excellent permeability. The PDB nanohydrogel has a small and uniform size distribution, no obvious aggregation, an average particle size of 124.9 nm, and a zeta potential of approximately -23.3 mV. Figure 2 (B, C). At 37℃, the PDB nanohydrogel exists in a gel state, but as the temperature decreases to 4℃, the PDB nanohydrogel gradually changes from a gel state to a liquid state. After heating to 37℃, the PDB nanohydrogel returns to a gel state. Figure 2 D). According to Figure 2 E. When the concentration of PDB nanohydrogel is 20 wt%, it transforms into a gel state at temperatures above 30°C, making it suitable for ocular gel drug delivery systems. Furthermore, good adhesion properties are crucial for ocular drug delivery systems. For example... Figure 2 As shown in Figure F, at 37°C, VAC-NPS is at 10 -4 Up to 10 -1 It exhibits a good viscosity distribution between Pa and s.
[0058] Example 2: Cell compatibility study of PDB nanohydrogels
[0059] In vitro cell experiments were conducted using logarithmically grown HCE-T cells (iCell Bioscience Inc.). The experiment consisted of a control group (HCE-T cells cultured under normal conditions) and a PDB group (HCE-T cells co-cultured with PDB nanogel). After 48 hours of incubation, calcein-AM (Sigma, USA) was added to the culture medium and incubated with the cells at 37°C for 15–30 minutes. The cells were then washed and observed under a fluorescence microscope.
[0060] To evaluate the cell compatibility of PDB nanohydrogel, an in vitro cell model was established using human corneal epithelial cells (HCE-T cells). HCE-T cells were co-cultured with PDB nanohydrogel for 48 h, and cell compatibility was assessed. Figure 2 The results in G indicate that cells can grow normally on the surface of the nanogel and are essentially stained with green fluorescence, suggesting that the PDB nanohydrogel has good cell compatibility.
[0061] Example 3: Construction and performance characterization of a PDB nanohydrogel corneal drug delivery system
[0062] PDB nanohydrogels were uniformly dispersed in PBS and stirred overnight to prepare a PDB nanohydrogel corneal drug delivery system. Then, pre-prepared gatifloxacin (Jiangsu Yunyang Pharmaceutical Co., Ltd., China) was added to the above solution and mixed thoroughly to form the PDB nanohydrogel drug delivery system.
[0063] (1) The morphology and pore distribution of drug-loaded PDB nanohydrogels were observed using scanning electron microscopy.
[0064] (2) The inverted test tube method was used to analyze the state of drug-loaded PDB nanohydrogel as a function of temperature.
[0065] (3) The particle size and zeta potential of the drug-loaded PDB nanohydrogel were measured using a laser particle size analyzer.
[0066] (4) The swelling rate of drug-loaded PDB nanohydrogels was determined using the PBS immersion method. A certain mass of dried hydrogel samples was taken, and the initial weight (W0) of each sample was measured. The samples were then immersed in PBS buffer solution and placed in a constant temperature and humidity incubator at 37°C and 90% humidity. At different immersion time points (3h, 6h, 12h, and 24h), the samples were removed, gently dried with absorbent paper, and weighed (Wi). The swelling rate was calculated using the following formula:
[0067] S rate%=(Wi-W0) / W0×100%
[0068] (5) The in vitro degradation capacity of the drug delivery hydrogel was investigated in simulated body fluids at pH 7.4 and 5.5. Samples were collected at different immersion time points (0d, 3d, 7d, 14d, 21d) and their weights were measured. The mass loss rate at each time point was calculated as the degradation rate of the material.
[0069] and Figure 2 Compared to the PDB nanohydrogel material shown in A, Figure 3 The microstructure of the PDB nanohydrogel loaded with gatifloxacin in A did not show significant changes and retained its porosity. Figure 3 As shown in BC, the drug-loaded PDB nanohydrogel has a Z-average size of 121.7 nm and a zeta potential of -24.1 mV. Furthermore, its thermosensitive properties remain unchanged. At 37 °C, the drug-loaded PDB nanohydrogel is in a gel state, and gradually transforms into a liquid state as the temperature drops to 4 °C. Figure 3 D). These data indicate that the properties of PDB nanohydrogels are largely unaffected after drug loading.
[0070] Example 4: Drug release study of PDB nanohydrogel corneal drug delivery system
[0071] The in vitro release behavior of drug-loaded nanohydrogels was studied using dialysis with pH 7.4 / 5.5 PBS as the release medium. 20 mg of lyophilized drug-loaded nanohydrogel sample was dispersed in 10 mL of pH 7.4 / 5.5 PBS solution. Then, 2 mL of the dispersion was added to a dialysis bag, sealed at both ends, and placed in a centrifuge tube containing 50 mL of release medium. The experiment was conducted at 37 °C with constant stirring at 60 rpm / min. 2 mL samples were collected at 0.5 h, 1 h, 2 h, 4 h, 6 h, 8 h, 12 h, and 24 h, with an equal volume of fresh culture medium added each time. Each experiment was performed in triplicate. The drug content in the release solution was determined by HPLC, and the cumulative release percentage (%) was calculated. A drug release curve was plotted with sampling time as the x-axis and cumulative release percentage as the y-axis.
[0072] Drug release is typically achieved through the swelling of hydrogels, which leads to an increase in porosity. The swelling ratio of a hydrogel is an important parameter for evaluating the rate and amount of drug release. Figure 3 As shown in Figure E, the swelling rate of the drug-loaded PDB nanohydrogel plateaued after approximately 12 hours, with a measured swelling rate of approximately 21.2%. This indicates that the drug-loaded nanohydrogel exhibits low swelling rate and minimal porosity change after water absorption, thus enabling slow and stable drug release. We further investigated the in vitro degradation rate and release behavior of the drug-loaded nanohydrogel under different pH conditions. Figure 3 As shown in Figure F, the drug-loaded PDB nanohydrogel exhibited good stability under simulated physiological conditions. After 21 days, the degradation rate in simulated body fluid at pH 5.5 was approximately 45.7%, while the degradation rate in simulated body fluid at pH 7.4 was approximately 37.8%. Figure 3 As shown in Figure E, the in vitro drug release behavior of the drug-loaded PDB nanohydrogel indicates that the drug release rate is significantly higher under acidic conditions compared to a neutral environment. Furthermore, the release behavior shows no burst release; the drug release rate is approximately 37.6% within 24 hours at pH 5.5 and approximately 16.2% at pH 7.4. These results demonstrate that the gatifloxacin-loaded PDB nanohydrogel exhibits good swelling properties, stability, and pH responsiveness, effectively prolonging the drug's residence time on the ocular surface and improving its bioavailability.
[0073] Example 5: In vivo targeted distribution and efficacy study of gatifloxacin-loaded controlled-release nanohydrogel for the treatment of bacterial keratitis.
[0074] A mouse model of bacterial keratitis was established using the corneal scratching inoculation method. Staphylococcus aureus (S. aureus) is one of the bacteria most commonly associated with bacterial keratitis in humans and was selected as the pathogen. Three-month-old mice were randomly divided into five groups: a control group, a Staphylococcus aureus group, a Staphylococcus aureus + gatifloxacin group, a Staphylococcus aureus + PDB group, and a Staphylococcus aureus + PDB + gatifloxacin group. Before surgery, mice were anesthetized, and Staphylococcus aureus (Solarbio, China) was locally scratched and inoculated onto the cornea of the right eye of each mouse to induce keratitis. Postoperatively, the bacterial infection was allowed to develop undisturbed for 24 hours prior to treatment. The control group and the Staphylococcus aureus group received PBS. The Staphylococcus aureus + gatifloxacin group, the Staphylococcus aureus + PDB group, and the Staphylococcus aureus + PDB + gatifloxacin group were administered gatifloxacin eye drops, 20wt% PDB nanogel, and 20wt% PDB nanogel + gatifloxacin eye drops, respectively. All treatments were administered at a dose of 5 μL, three times daily for two consecutive days. After treatment, mice were euthanized, and the corneas were excised and stained with hematoxylin and eosin to observe morphological changes in each group. During this period, tears were collected and cultured on agar plates to evaluate the antibacterial effects of different treatments.
[0075] A normal cornea is a transparent membrane that forms the anterior surface of the eyeball, composed of corneal epithelium, stroma, and endothelial cell layer.
[0076] like Figure 4 As shown in Figure A, the cornea in the model group exhibited significant opacity, lack of basal cells, interrupted intercellular connections, increased intercellular spaces, uneven cell size, and severe keratinization. Inflammatory cell infiltration and neovascularization were observed in the corneal stroma. Compared to the model group, the positive control group showed mild opacity with no significant increase in thickness, but still exhibited mild keratinization, interrupted epithelial cell connections, and enlarged intercellular spaces. After treatment, the PDB nanohydrogel group showed no significant change in corneal thickness, but the interrupted intercellular connections, enlarged intercellular spaces, and keratinization were alleviated, showing slight improvement. Compared to the model group, the gatifloxacin-loaded PDB nanohydrogel group showed significant improvement in corneal opacity, reduced corneal thickness, no significant keratinization, and improved intercellular connections, increased intercellular spaces, and uneven cell size.
[0077] During this period, tears were collected and incubated on agar plates to evaluate the antibacterial effects of various treatments. Results are as follows: Figure 4As shown in Figure B, compared with the control group, the number of Staphylococcus aureus in the tear fluid of the model group was significantly increased. However, gatifloxacin, PDB nanohydrogel, and gatifloxacin-loaded PDB nanohydrogel all showed varying degrees of inhibitory effects on the growth of Staphylococcus aureus in the tear fluid, with the gatifloxacin-loaded PDB nanohydrogel exhibiting the best inhibitory effect. These results indicate that PDB nanohydrogel can serve as an excellent sustained-release system for gatifloxacin, prolonging the drug's duration of action and enhancing its efficacy. Furthermore, PDB nanohydrogel possesses good biocompatibility, significantly improving the efficacy of gatifloxacin in treating bacterial keratitis.
[0078] The technical innovation of this invention lies in:
[0079] 1. Borax was used as a catalyst to induce a thiol-olefin Michael-type polyaddition reaction of PEG. Borax is a highly efficient catalyst, enabling rapid gelation at room temperature (from 40 s to 2 min). Essentially, borax, as a catalyst, can simultaneously form two types of bonds: covalent thioether bonds and transient borate ester bonds. Due to the dynamic nature of the borate ester bonds, the gel exhibits self-healing properties, healing within 30 min without external stimulation. The multiple advantages of borax open up a new avenue for the preparation of nanohydrogels.
[0080] 2. PDB nanohydrogel drug delivery system combined with antibiotic drugs. Under appropriate ratio control, PDB nanohydrogels exhibit sensitive temperature-sensitive and pH-responsive properties. Before instillation, they exist as a homogeneous liquid and are applied to the ocular surface as eye drops. Upon application, they rapidly cross-link under temperature, forming a stable three-dimensional network structure that encapsulates the drug. Furthermore, due to their pH responsiveness, drug release is accelerated under acidic conditions and virtually nonexistent under neutral conditions, further enhancing the pH specificity of drug release.
[0081] 3. Gatifloxacin, an antibiotic, is used as a targeted therapy for bacterial keratitis. The nano-hydrogel, through local coverage, provides continuous and controllable release and distribution of gatifloxacin at the infected site, ensuring effective drug delivery into cells and direct delivery to the infection site. This reduces the required dosage, improves bioavailability, and lowers toxic side effects.
[0082] The above description is merely one embodiment of the present invention and is not intended to limit the present invention in any other way. Any person skilled in the art can make changes or modifications to the above-disclosed technical content to create equivalent embodiments. However, any simple modifications, equivalent changes, and improvements made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A controllable nanohydrogel drug delivery system loaded with gatifloxacin, characterized in that, The nanohydrogel is formed by using borax as a catalyst, through the polymerization reaction between polyethylene glycol diacrylate (PEGDA) and dithiothreitol (DTT), and the complexation reaction between DTT and borate anion (B(OH)4-) and 1,2-diol, to form a three-dimensional cross-linked polyethylene glycol-dithiothreitol-boric acid (PDB) nanohydrogel network.
2. The drug delivery system according to claim 1, characterized in that, The average particle size of the PDB nanohydrogel loaded with gatifloxacin was approximately 121.7 nm, and the Zeta potential was approximately -24.1 mV.
3. The drug delivery system according to claim 1, characterized in that, The drug-loaded PDB nanohydrogel is in a gel state at 37°C and gradually transforms into a liquid state as the temperature drops to 4°C.
4. The drug delivery system according to claim 1, characterized in that, The drug-loaded PDB nanohydrogel is pH-responsive, with a higher drug release rate at pH 5.5 than at pH 7.
4.
5. The drug delivery system according to claim 1, characterized in that, The swelling rate of the drug-loaded PDB nanohydrogel reached a plateau after about 12 hours, with a measured swelling rate of approximately 21.2%.
6. The drug delivery system according to claim 1, characterized in that, PDB nanohydrogels were uniformly dispersed in PBS at 4°C and stirred overnight. Then, gatifloxacin was added to the mixture at 4°C and thoroughly mixed to prepare a PDB nanohydrogel drug delivery system.
7. A method for preparing a controllable nanohydrogel drug delivery system loaded with gatifloxacin as described in any one of claims 1-6, characterized in that, The preparation method of PDB nanohydrogel includes the following steps: (1) Dissolve 0.14 mM PEGDA and 0.14 mM DTT in 0.5 mL of water; (2) Add 0.5 mL of 0.04 mmol / L sodium borate solution, mix thoroughly, and keep the solution at room temperature for a short time to obtain PDB nanohydrogel.
8. The use of the PDB nanohydrogel drug delivery system loaded with gatifloxacin according to any one of claims 1-6 in the preparation of eye drops for treating bacterial keratitis.